THE ROLE OF REMOTE SENSING AND SIG DATA FOR MAPPING LAND PRICE ESTIMATION IN PAYAKUMBUH CITY - Ramanda, Risa; Syahar, Fitriana; Antomi, Yudi; Ramadhan, Risky (International Remote Sensing Applied Journal, 2023)
Land is a field that has a strategic role in the development of an urban area, land located in a strategic location of economic activity, easy accessibility, and complete infrastructure can be said that the land has a high land price. Factors that influence land prices in urban areas are increasing population, land change, and regional development. Payakumbuh City is a city that is strategically located and close to the city center, has complete public facilities, adequate road access, proximity of land to economic areas, and urban development and buildings affect land prices in Payakumbuh City. The research objectives (1) identify factors that affect land prices in Payakumbuh City (2) analyze the spatial distribution of land price estimates in Payakumbuh City. The research method to determine land price estimation is the overlay and weighting method. The parameters used in this study are land use using Pleiades imagery, land accessibility, and completeness of public facilities. Based on the results of the research, the factors that affect land prices in Payakumbuh City are land use that is closer to the city center will be more expensive, land accessibility that facilitates road access, and completeness of public facilities. Based on the results of data processing, it is found that there are 4 classes of land price estimation in Payakumbuh City, namely the very high class has a price of Rp. 5,000,000.00 - Rp. 10,000,000.00, the high class has a land price of Rp. 2,000,000.00 - Rp. 5,000,000.00, the medium class has a land price of Rp. 1,000,000.00 - Rp. 2,000,000.00, and the low class has a land price of Rp. 200,000.00 - Rp. 500,000.00.